2015
DOI: 10.1007/s00709-015-0862-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic acid allelochemicals induced morphological, ultrastructural, and cytological modification on Cassia sophera L. and Allium cepa L.

Abstract: The allelopathic potential of leaf aqueous extract (LAE) of Calotropis procera on growth behavior, ultrastructural changes on Cassia sophera L., and cytological changes on Allium cepa L. was investigated. LAE at different concentrations (0.5, 1, 2, and 4 %) significantly reduced the root length, shoot length, and dry biomass of C. sophera. Besides, the ultrastructural changes (through scanning electron microscopy, SEM) induced in epidermal cells of 15-day-old seedlings of Cassia leaf were also noticed. The cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…This type of concentration-dependent inhibition has been reported by Sinha and Samar (2004), Swain et al (2005), Ishak and Sahid (2014), Gulzar et al (2016), Al-Harbi (2018, Mushtaq et al (2018), Zaman et al (2020), andHossen et al (2020). The extracts of A. catechu had different inhibitory activities on different tested plants, showing that the growth inhibitory effects of this plant's extracts depended on the target plant species.…”
Section: Discussionsupporting
confidence: 75%
“…This type of concentration-dependent inhibition has been reported by Sinha and Samar (2004), Swain et al (2005), Ishak and Sahid (2014), Gulzar et al (2016), Al-Harbi (2018, Mushtaq et al (2018), Zaman et al (2020), andHossen et al (2020). The extracts of A. catechu had different inhibitory activities on different tested plants, showing that the growth inhibitory effects of this plant's extracts depended on the target plant species.…”
Section: Discussionsupporting
confidence: 75%
“…Several previous studies have also reported that the inhibitory effect of plant extracts is more pronounced on root growth than shoot growth (Liu et al, 2018;Sbai et al, 2016). Such root inhibition might be due to the higher permeability of root tissue, which allows more allelochemicals to enter the roots compared with shoots because the shoot surface is covered with a well-developed cuticular layer, whereas the root surface lacks this layer (Gulzar et al, 2016;Yoshimura et al, 2011). Another possible explanation is that root growth largely depends on cell proliferation, which is All the test plant species were treated at the concentrations of 0.001, 0.003, 0.01, 0.03, 0.1, and 0.3 g dry weight equivalent extract of G. pedunculata/mL.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the cotyledon of seeds appeared abnormal compared to root formation in the seedlings in the control. Primary growth of plants is extremely sensitive to the concentration of bioactive compounds in their surrounding [17]. The effect of allelochemicals in E. coccinea may have led to the metabolic impairment of mung bean which resulted decreasing formation of normal root.…”
Section: Radicle and Shoot Length Of Mung Bean (Vigna Radiata)mentioning
confidence: 99%